Peran Komisi Yudisial Dalam Menegakkan Keluhuran Martabat Hakim - Indah Radiawati; Burhanuddin Burhanuddin (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to determine the role of the Judicial Commission in supervising judges. The authority of the Judicial Commission in overseeing the behavior of judges in the context of upholding honor and dignity as well as maintaining the behavior of judges and also the position and implementation of the supervisory function for judges in order to realize an independent judicial function to uphold law and justice for all Indonesian people. In addition, so that each judge can behave properly and fairly in dealing with a clean judiciary and in accordance with what has been regulated in the legislation. The research method used is normative juridical, namely research that focuses on studying the application of a norm or rule of law. The results showed that the Judicial Commission is an independent judicial body, where the Judicial Commission has the authority to supervise judges and maintain and uphold the honor, nobleness, and behavior of judges. Community elements can also be involved in monitoring, so that politicization of Supreme Court judges can be reduced.Keywords: Oversight, Judicial Commission, Judge